An analysis of the importance of management research topics to academics and chief executives in New Zealand and Canada - Cartner, Monica (School of Management Working Papers, 1991)
This paper reports on a survey in July 1990 to ascertain and compare the views of chief executives and academics in co=erce and administration in New Zealand concerning management research topics, and to compare these with one done concurrently in Canada. The survey was by means of a postal questionnaire developed by Paul Bergman at the University of Western Ontario and respondents were asked to rate forty-three research topics on a five point Likertscale, according to their view of the topic’s importance to management research in their respective countries. The analysis of results provides a comparative ranking of the importance of the research topics and of significant differences in the rating of therr importance to the four groups. The pattern with respect to the ranking of topics’ importance is of broad similarity and five topics - quality of customer service, strateipc planning and mana ement, international competitiveness, managing technological change and fostenng organisational innovation - are ranked in the top ten topics by all four groups. The differences found in ranking and importance ratings suggest a mainly intraorganisational focus by chief executives and a wider focus, in particular taking more account of governmental policy topics, by academics.